Growing Resistance by Emily Eaton - Taarini Chopra (Canadian Food Studies, 2014)
The short history of genetically modified (GM) crops in Canada has been defined by controversy, debates about health and environmental concerns, and deeply entrenched corporate control. The past fifteen years have seen numerous approvals of new GM crop varieties, while just a handful have been stopped from reaching the market. One of these unusual cases is the subject of Emily Eaton's new book Growing Resistance. In this compelling volume, Eaton questions why the introduction of GM wheat was met with such strong opposition from Canadian farmers, while GM canola had been widely adopted just a decade earlier. Her analysis goes beyond a cost-benefit assessment of the two crops to include their biological differences, and dig into the rich historical and cultural role that wheat has played for Prairie farmers. Taken together, Eaton argues, these factors explain the fervent public opposition to the introduction of GM wheat in the Prairies, and Monsanto's consequent decision to withdraw its request for government approval of herbicide tolerant wheat and discontinue its research and breeding program.